A novel Fe-La-Ce tri-metallic composite for the removal of fluoride ions from aqueous media. (1st February 2018) - Thathsara, S.K.T.; Cooray, P.L.A.T.; Mudiyanselage, Thilini Kuruwita; Kottegoda, Nilwala; Ratnaweera, Dilru R.
Highlights: The maximum adsorption capacity (303.03 mg/g at pH 4.00) was higher than the most reported fluoride adsorbents. Careful composition analysis has confirmed that detectable levels of these metals has not leached to aqueous environments. The minimal interference for the fluoride adsorption were observed from chloride ions and sulphate ions. Fe-La-Ce tri-metallic composite exhibits excellent regeneration (desorption is 96.13%) and reusability, hence this could be an ideal adsorbent for fluoride ions.